Is dry bulk shipping still worth investing in? - Tan, Kenneth Jia Jun (2017)
In the past few years, the Capesize market had never shown optimistic signs of recovering to the freight levels of the dry bulk shipping boom in 2008. However, it remains to be seen whether the returns from investing in Capesize vessels in this current depressed market would represent a worthy investment. Past literatures have identified the complications of the dry bulk industry and how its fundamentals continue to leave one pondering; when is it the right time to invest in the dry bulk industry? In this paper, a hypothesis is proposed based on the Capesize market given the validation of several chosen variables, which will provide a clearer picture on the future of the Capesize vessel. Both quantitative and qualitative approaches were applied in the process, with quantitative forecasts generated based on historical market research conducted on the dry bulk market and garnering responses from survey questionnaires sent out to various shipping professionals to unearth qualitative sentiments on the Capesize market. The results of the validation of the hypothesis could prove constructive for keen investors in contemplating the possible opportunities in investing in the Capesize market for future years to come.